A Review of Capital Budgeting Practices - Jacobs, Davina (Washington, D.C. : International Monetary Fund, 2008)
A key challenge in government budgeting is to define an appropriate balance between current and capital expenditures. Budgeting for government capital investment also remains not well-integrated into the formal budget preparation process in many countries. This paper aims to provide an overview of past and current budgeting practices for public investment. The study will also provide a comparison between the budget practices between low-income countries and developed countries and make a series of recommendations for how to ensure efficient integration of capital planning and budget management in low-income countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet